Mapping Husbands’ Social Perceptions on Women’s Reproductive Health: A Systematic Review - Dewi Puspitaningrum; Mohammad Irsam; Endah Sulistyowati (Universitas Muhammadiyah Semarang, 2026)
Background: Husbands’ perceptions significantly influence women’s reproductive health, affecting healthcare-seeking behavior, contraceptive use, antenatal care participation, and maternal outcomes. However, comprehensive mapping of these social perceptions remains limited. Objective: To systematically map and synthesize evidence on husbands’ social perceptions toward women’s reproductive health across diverse cultural settings. Methods: A systematic review was conducted following PRISMA guidelines. Literature was searched from Scopus, PubMed, Web of Science, and ScienceDirect databases for articles published between 2021–2025. Keywords used included “husband perception,” “social perception,” “women’s reproductive health,” and “men involvement.” Studies included were qualitative, quantitative, and mixed-method research focusing on husbands’ perceptions regarding women’s reproductive health in low- and middle-income countries (LMICs) and high-income countries (HICs). Data were extracted and thematically synthesized. Results: From 312 identified articles, 6 studies met the inclusion criteria. Three primary themes emerged: (1) Husbands’ knowledge and misconceptions about reproductive health (contraception, maternal care, menstrual health), (2) Cultural and religious beliefs shaping perceptions toward women’s reproductive health, and (3) Husbands’ perceived roles and decision-making power in women’s reproductive healthcare-seeking behaviors. Studies in LMICs reported that patriarchal norms and low health literacy among husbands contribute to delayed reproductive healthcare access. In contrast, studies from HICs highlighted shared decision-making and supportive roles, yet gaps in specific reproductive health knowledge persisted. Conclusion: Husbands’ social perceptions significantly impact women’s reproductive health outcomes. Addressing misconceptions, promoting health literacy, and engaging husbands in reproductive health programs are crucial to improving maternal and reproductive health outcomes globally. Future interventions should integrate culturally sensitive strategies to enhance husbands’ positive involvement in women’s reproductive health.